1991
DOI: 10.1002/jnr.490300111
|View full text |Cite
|
Sign up to set email alerts
|

NF‐L and peripherin immunoreactivities define distinct classes of rat sensory ganglion cells

Abstract: Double immunofluorescence studies using antibodies against NF-L and peripherin revealed three distinct subpopulations of neurons in rat dorsal root ganglia (DRG). In the adult rat, 46% of the DRG neurons were small and peripherin-positive (NF-L-negative), and 48% were large and NF-L-positive (peripherin-negative). About 6% were both peripherin- and NF-L-positive. All of the DRG neurons reacted with antibodies to NF-M and nonphosphorylation-dependent or phosphorylation-independent antibodies to NF-H. The neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
120
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 49 publications
18
120
0
3
Order By: Relevance
“…The current report is the first, however, to recognize that the change in diameter occurs in conjunction with a shift in axons from the ONLo to the ONLi. Peripherin expression correlates with small axonal diameter elsewhere, such as spinal cord dorsal roots (Goldstein et al, 1991). Our results are consistent with these reports and suggest that peripherin may serve to limit axonal caliber in the ONLo as axons exhibit rapid growth.…”
Section: Potential Roles Of Intermediate Filamentssupporting
confidence: 91%
“…The current report is the first, however, to recognize that the change in diameter occurs in conjunction with a shift in axons from the ONLo to the ONLi. Peripherin expression correlates with small axonal diameter elsewhere, such as spinal cord dorsal roots (Goldstein et al, 1991). Our results are consistent with these reports and suggest that peripherin may serve to limit axonal caliber in the ONLo as axons exhibit rapid growth.…”
Section: Potential Roles Of Intermediate Filamentssupporting
confidence: 91%
“…5). Double labeling with anti-peripherin was used to analyze the populations of neurons expressing these two TTX-R channels in small DRG neurons (25). As reported previously (26), we observed that Na v 1.8 (Fig.…”
Section: Na V 19 Expression and Subcellular Localization Are Alteredsupporting
confidence: 77%
“…ASIC antibodies were used alone or with markers specific for small diameter (17) or for medium-to large-diameter cells (18). Fig.…”
Section: Resultsmentioning
confidence: 99%